Pengaplikasian Program ZIN untuk Perencanaan Manajemen Sistem Jaringan Jalan di Kota Makassar - Muhammad Isran Ramli; S. A. Adisasmita; Mubassirang Pasra; Hajriyanti Yatmar (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Transportation problems have an important role due to population and economic growth. The population of that simultaneity with the vehicle growth factor without the inadequate facilities is one of the factors that contribute to the traffic problems. The mitigation is needed to prevent other transportation problems. Makassar is one of the Metropolitan City has a vehicle’s growth factor 13-14 percent every year for motorcycle and 8 – 10 percent for every year; due to this condition, the critical networks frequently saw in the road would be disrupted. The level of service (LOS) of road decreased. The information about the LOS basically formulated by the Indonesia Highway Capacity Manual (IHCM) as guidance needs basic survey data such as vehicle volume, speed gun test result, geometric condition, and others as supporting data. Basically, the manual calculation using ICHM can be formulated with effective and efficient using application ZIN. The application of ZIN as one of the planning management to find the more efficient for more road network, especially for Makassar.